Pengaruh Environmental, Social and Governance (ESG) Risk dan Enterprise Risk Management (ERM) terhadap Kinerja Perusahaan - Irwansyah, Irwansyah; Sebrina, Nurzi (Universitas Negeri Padang, 2024)
This study examines the effect of ESG Risk and ERM on company performance. The population used in this study are companies listed on the Indonesia Stock Exchange in 2023. The sampling technique in this study is purposive sampling, where 77 companies pass. The data used is secondary data, including ESG Risk scores from Morningstar Sustainalytics, risk management disclosures, and financial and non-financial data obtained from the official website of the Indonesia Stock Exchange and the company's annual report. Company performance is measured using return on assets (ROA). The results showed that the ESG Risk of companies listed on the Indonesia Stock Exchange does not affect company performance. In contrast, ERM, as measured by disclosure items, negatively influences firm performance. These findings provide new insights into the relationship between risk management, ESG factors, and financial performance in the context of the Indonesian capital market.